A System and Method for improving the Model Based Systems Engineering Environment capability. (4th December 2019) - Prasanna Kumar, R N; Patil, Shailesh
Abstract: As the evolution of new technologies such as IOT and Cloud Computational Analysis continue, the Systems have become more and more complex and it is grown much in size. Unfortunately the present day SE Environments, Modeling languages and the related tool sets are not sufficient enough to represent the multiple streams problem at hand in one integrated modeling environment which makes all of the Stakeholders and Engineers & Non‐engineers understand the problem scenarios. This lack of integrated modelling environment and a methodology for an additional representation of multiple problem domains limits off the analysis capabilities, timely communication of the technical and project risks to various stakeholders for decision making. It happens due to the inherent capability & limitations of each modeling languages followed so far by the Model Based System Engineering (MBSE) community & to bridge across them. This research paper focuses on improving the SE modeling environment capability from at least three distinct directions. First, it proposes a way to strengthen the SysML semantics with concrete guidelines which helps to reduce the incompleteness & ambiguous nature of the SysML elements especially in the Non Functional Requirements modeling. Then it explores the possibility of integrating the ontology aspects offered in evolving Life‐cycle Modeling Language (LML) specification to an extended SysML profile to complement its constructs to facilitate communication with non‐system engineers as well. Finally, this paper draws parallel between the LML architectural modeling concepts with the Architecture Analysis & Design Language (AADL) constructs and realizes them in an extended SysML profile. This will facilitate the seamless flow of models at various abstraction levels & translation of architectural model information from LML to AADL analytical environment. A case study implemented using an extended SysML profile & a methodology will be presented to measure its effectiveness.